Pengaruh Coating Lidah Buaya dengan Penambahan Karagenan terhadap Umur Simpan Jambu Kristal Selama Penyimpanan - Angraeni, Rini; Tamrin, Tamrin; Asmara, Sandi; Warji, Warji (abe.fp.unila.ac.id, 2023)
This research was conducted to observe the effect of edible coating aloe verawith a combination of carrageenan concentration on the shelf life of crystal guava fruit. This study was designed using linear regression consisting of 2 factors. The first factor consists of 3 levels of carrageenan concentration which includes K1 = 0.1% , K2 = 0.2% , K3 = 0.3% . The second factor is the variation of storage temperature which consists of 2 levels, namely storage at room temperature 27℃ and cold temperature 11℃. The application of edible coating of crystal guava fruit with a layer of aloe vera gel and carrageenan has an effect on maintaining the quality of crystal guava fruit against weight loss, green skin color, hardness, total dissolved solids, water content and organoleptic test of storage taste (room temperature) of crystal guava fruit to age. keep 6 days and storage (low temperature) crystal guava fruit up to a shelf life of 9 days after application. K3 treatment (carrageenan concentration 0.3%) can be used to maintain the quality of crystal guava fruit during storage. Keywords: Carrageenan, Edible Coating, Stronge Temperature, Sweet Seedless Guava